BET-independent MLV-based Vectors Target Away From Promoters and Regulatory Elements - Sara El Ashkar; Jan De Rijck; Jonas Demeulemeester; Sofie Vets; Paradise Madlala; Katerina Cermakova; Zeger Debyser; Rik Gijsbers (Elsevier, 2014)
Stable integration in the host genome renders murine leukemia virus (MLV)-derived vectors attractive tools for gene therapy. Adverse events in otherwise successful clinical trials caused by proto-oncogene activation due to vector integration hamper their application. MLV and MLV-based vectors integrate near strong enhancers, active promoters, and transcription start sites (TSS) through specific interaction of MLV integrase (IN) with the bromodomain and extra-terminal (BET) family of proteins, accounting for insertional mutagenesis. We identified a BET-interaction motif in the C-terminal tail of MLV IN conserved among gammaretroviruses. By deletion of this motif or a single point mutation (INW390A), BET-independent MLV (BinMLV) were engineered. BinMLV vectors carrying INW390A integrate at wild-type efficiency, with an integration profile that no longer correlates with BET chromatin distribution nor with the traditional markers of MLV integration. In particular, BinMLV vector integration associated less with oncogene TSS compared to the MLV vectors currently used in clinical trials. Together, these findings open perspectives to increase the biosafety of gammaretroviral vectors for gene therapy.